SHANK-regulation of drug sensitivity in KRAS-driven cancer - Farahani, Iman (My University, 2022)
Ras proteins are intracellular GTPase switch proteins activating MAPK/ERK signaling pathways in their active GTP-bound forms. Mutant KRAS oncoproteins are mostly in their active state, fostering ERK-dependent cell proliferation in cancer. SHANK1 and SHANK3 proteins interact with GTP-bound active wild-type and mutant Ras family members, including mutant KRAS, through their Ras/Rap-association (RA) domain. Due to the clinical significance of KRAS mutations in cancer, KRAS targeting has been a long-standing objective in cancer therapy. In this study, I used short interfering RNAs (siRNAs) to silent SHANK1 and SHANK3 genes in KRAS-mutant cancer cells. Then I compared the effects of SHANK1 and SHANK3 depletion on KRAS-mutant cancer cell proliferation and MAPK activity. I found that, unlike SHANK1, loss of SHANK3 dysregulates MAPK signaling through ERK hyperactivation leading to apoptosis. Also, I validated results from a recent cell-based High-Throughput Screen (HTS) designed to uncover drug sensitivities augmented by SHANK3 depletion in KRAS-mutant pancreatic cancer. Through cell viability assay, I found that the estimated IC50 of a selected subset of inhibitors, identified in the screen, is changed in SHANK3 depleted condition. Further investigations are required for discovering the underlying mechanisms of action of SHANK3 depletion, sensitizing cells to or rescuing them from the apoptotic effects of the inhibitors.
Keywords: mutant KRAS, MAPK pathway, SHANK proteins